Morphometric Study of Lateral Ventricles of Brain by MRI in Healthy Adults in Northern Zone of Bangladesh (Ibrahim Cardiac Medical Journal, 2021)
Background & Objective: The present study was done to provide information about the morphometric measurement of lateral ventricles of human brain in relation to age and sex in northern Bangladeshi people.Methods: This cross-sectional study was conducted in the Department of Anatomy, Rajshahi Medical College, Rajshahi over a period one year from July 2014 to June 2015. All patients attending at Radiology & Imaging Department of Rajshahi Medical College Hospital and at different private hospitals and clinics of Rajshahi city and had normal MRI scan of brain were the study population. A total of 60 individuals of both sexes and age ranging between 18-50 years were included in the study. Having obtained ethical clearance from the Ethical Committee and verbal consent from the patients, the data collection was commenced. Patients were asked to lie on the MRI table in supine position with head fixed and coil placed around the head. MRI was done with MRI machine (Airis II Hitachi 0.3 Tesla) and images were taken by T1WI, T2WI, STAIR, FLAIR. Images were taken from axial, sagittal and coronal planes with sequence slice thickness being 7 mm. From the images of axial slices, six proper slices were selected.Result: Age distribution of the subjects with respect to sex shows that nearly two-thirds (63.3%) of the female subjects were 30 or younger than 30 years old, whereas 50% of the male subjects were early middle-aged (p = 0.110). The mean lengths of frontal horn of right and left lateral ventricles in male subjects were significantly greater than those in female subjects (p = 0.002 and p = 0.001 respectively). Likewise, the right and left ventricular bodies in male subjects were significantly longer than those of their female counterparts (p = 0.033 and p = 0.012 respectively). The length of frontal horn of the lateral ventricles was found to increase with age up to 40 years in both right and left ventricles and then it began to decrease. The mean lengths of frontal horn of right and left lateral ventricles at ages ≤ 30, 31-40 and > 40 years were 27.25, 28.74 and 26.0 mm and 27.57, 28.93 and 27.19 mm respectively. While the three measures of length of frontal horn of right lateral ventricles were significantly heterogeneous (p = 0.049), the three measures of length of frontal horn of left lateral ventricles were not significantly different (p = 0.141).The mean lengths of body of right and left lateral ventricles at different ages were 40.40, 43.98, 45.11 mm and 41.06, 44.52 and 45.21 mm respectively (p = 0.001 andp = 0.001 respectively).Conclusion: The present study concluded that the lateral ventricles vary in size within certain limit according to age, sex and laterality. All the parameters of lateral ventricles (lengths of frontal horn, length of ventricular body) were significantly larger in males than those in females. While the length of frontal horn of the lateral ventricles (of both sides) increases in size up to the age of 40 years and thereafter regresses, the length of ventricular body bears a linear relationship with age throughout life-span.Ibrahim Card Med J 2020; 10 (1&2): 45-50